Properties and flexural behavior of self-compacting concrete with added coir fiber and POFA - Iman, Afif; Mohamad, N; Raain, Fasya; Sofia, Anis; Mydin, Azree; Samad, A A A
This paper presents the mechanical properties and flexural behavior of selfcompacting concrete (SCC) with addition of 0.2%, 0.4% and 0.6% coir fiber (CF) as filler, and 10% palm oil fuel ash (POFA) as partial cement replacement. Fresh SCC-POFA-CF mixture was tested under slump flow and J-ring tests to determine its workability. SCC-POFA-CF cubes and cylinders were tested under compressive and tensile tests to determine its compressive strength, tensile strength, and flexural strength, while prisms were tested under four point bending load to determine its flexural behavior. It is found that workability of SCC-POFA-CF decreased when CF increased. The optimum percentage of CF in SCC mixture was found to be 0.4%. SCC-POFA-CF experienced less crack compared to the control specimen. This shows that CF in SCC prisms managed to control the crack propagation.